2000
DOI: 10.1002/1529-0131(200001)43:1<14::aid-anr3>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Response to methotrexate treatment is associated with reduced mortality in patients with severe rheumatoid arthritis

Abstract: Patients with severe RA who do not respond to MTX treatment have a poor prognosis, with >4-fold increased mortality compared with the general population, while RA patients who respond to MTX treatment have only a moderately increased mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0
9

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(92 citation statements)
references
References 29 publications
(22 reference statements)
8
72
0
9
Order By: Relevance
“…However, this statement has been questioned and the diverging results are thought to be due to different study designs (15). Treatment with MTX was found to reduce mortality in patients with RA (16,17). As MTX was not commonly used during the first 5-10 years of the present study, we could not perform a corresponding analysis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, this statement has been questioned and the diverging results are thought to be due to different study designs (15). Treatment with MTX was found to reduce mortality in patients with RA (16,17). As MTX was not commonly used during the first 5-10 years of the present study, we could not perform a corresponding analysis.…”
Section: Discussionmentioning
confidence: 80%
“…Krause et al (16) found that a sufficient response to methotrexate (MTX) treatment was associated with decreased mortality in patients with severe RA, although the mortality rate remained only modestly increased compared to that in patients with severe RA not responding to MTX (SMR 1.64 vs. 4.11, respectively). MTX has also been shown to provide a survival benefit largely by reducing cardiovascular mortality (17).…”
mentioning
confidence: 99%
“…In addition, it was recently demonstrated that a response to MTX was related to reduced mortality in patients with severe RA. 35 Because we could assume we had collected most of the cases of lymphoma appearing in RA patients treated with MTX in France, we estimated the annual incidence of NHL in these patients (16.7 ϫ 10 Ϫ5 in women and 33.3 ϫ 10 Ϫ5 in men). No significant increased risk of NHL with the French NHL incidence was observed, 23 with an SMR close to 1, after adjustment for sex and age.…”
Section: Discussionmentioning
confidence: 99%
“…It appears likely that improved physical function would be associated with improved survival, based on pioneering studies of improved mortality outcomes associated with methotrexate treatment by Krause 46 and Choi 47 , as well as with biologic agents by Jacobsson 48 . Improvement in physical function scores with these agents is well established.…”
Section: Rheumatologymentioning
confidence: 99%